2014
DOI: 10.1016/j.virol.2013.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated retroviral GAG gene in Drosophila: New functions for an old gene

Abstract: The domestication of foreign genes is a powerful mechanism for new gene formation and genome evolution. It is known that domesticated retroviral gag genes in mammals not only take part in protecting against viral infection but also control cell division, apoptosis, function of the placenta, and other biological processes. In this study, we focused on the domesticated retroviral gag gene homolog (Grp) in the Drosophila melanogaster genome. According to the results of a bioinformatic analysis, the Grp gene produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Gagr homologs are found in all sequenced genomes of the genus Drosophila; their structure is maintained by stabilizing selection, which indicates the important function of the Gagr gene. Earlier, we have shown that, despite a high conservatism of the gene structure as a whole, its individual sections are under the influence of motif selection, as a result of which the products of the Gagr gene and its homologs from the melanogaster subgroup evolved towards the acquisition of a transmembrane domain [17]. At the same time, as shown in the present work, the promoter region of the gene underwent evolution, and as a result, binding sites for the transcription factor STAT appeared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gagr homologs are found in all sequenced genomes of the genus Drosophila; their structure is maintained by stabilizing selection, which indicates the important function of the Gagr gene. Earlier, we have shown that, despite a high conservatism of the gene structure as a whole, its individual sections are under the influence of motif selection, as a result of which the products of the Gagr gene and its homologs from the melanogaster subgroup evolved towards the acquisition of a transmembrane domain [17]. At the same time, as shown in the present work, the promoter region of the gene underwent evolution, and as a result, binding sites for the transcription factor STAT appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila studies allow us to expand our understanding of the role of domesticated genes of retroelements in the host organism. Drosophila has two examples of domestication of the env and gag genes of LTR-retrotransposons -the Iris and Gagr genes, respectively [17,58]. Gagr homologs are found in all sequenced genomes of the genus Drosophila; their structure is maintained by stabilizing selection, which indicates the important function of the Gagr gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. melanogaster could be a good model for such research because its genome contains both gag and env homologs. It has been shown that both genes are under strong selection [51,52]. Currently, their functions are being actively studied, and it is possible that both genes are involved in the defense against viral infections.…”
Section: Consequences Of the Retroelement Transpositionmentioning
confidence: 99%
“…Interestingly, it should be noted that gag - and env -related sequences were identified in Drosophila genomes [ 8 , 9 ] mirroring viral gene domestication events described in vertebrates. However, the cellular roles of these Drosophila putative proteins remain to be demonstrated.…”
Section: Gypsy: An Errantivirus Of Drmentioning
confidence: 99%